Monitoring and field data acquisition system for hybrid static concentrator plant. (February 2017) - Reatti, A.; Kazimierczuk, M.K.; Catelani, M.; Ciani, L.
Highlights: A solar photovoltaic and thermal concentrator plant is presented. A monitoring system is carried out in order to optimize both plant's performances and availability. The monitoring system allows to remote data analysis. Abstract: After the past Fukushima nuclear crisis, the renewable energy industry has been growing remarkably over the last years and has given a further incentive worldwide. In this context, the solar energy is one of the more accessible and cheaper energy resources. For this reason, the solar energy industry has seen a rapid expansion in the last ten years with the result that the share of electricity produced by this technology increases continuously. In order to optimize the photovoltaic energy costs, many solutions have been proposed. In particular, solar concentrating systems have been introduced with the scope of the reduction of silicon needed when compared to the traditional linear photovoltaic modules. This paper is focused on the development of a monitoring system for a hybrid (photovoltaic and thermal – PV/T) static concentrator plant that is able to monitor both electrical and thermal characteristics acquired from the solar and thermal plant. The monitoring of plant parameters is a very important task that can be achieved by means of a well-designed monitoring of system parameters. This approach allows for improving complex system maintenance policies and, at the same time, to achieve a reduction of unexpected failure occurrences in the most critical components, reducing the operating cost.